2015
DOI: 10.1364/ao.54.000895
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a widely tunable microwave signal generator based on dual-polarization fiber grating laser

Abstract: In this paper, we demonstrate the implementation of a widely tunable microwave signal generator based on a dual-polarization fiber grating laser. The laser contains two strong, wavelength-matched Bragg gratings photoinscribed in an Er-doped fiber and emits two polarization modes when pumped with a 980 nm laser diode. By beating the two modes, a microwave signal with a signal-to-noise ratio over 60 dB can be obtained. For a free running laser the fluctuations in intensity and frequency of the microwave signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Distributed-feedback (DFB) fiber lasers are appealing sources for various applications, notably because they offer a combination of low linewidth and high power [1]. When operating in a regime of simultaneous emission of two orthogonal eigenstates, such short-cavity lasers can be considered as microwave-optical sources, since the typical beat frequency between the two polarization modes is in the GHz range [2][3][4][5][6][7][8][9]. In this context, the stabilization of the beat frequency, in order to reduce the phase noise in microwave photonic links, is a question that led recently to develop an optical phase-locked loop scheme [9], and to the use of frequency-shifted optical feedback [10].…”
Section: Introductionmentioning
confidence: 99%
“…Distributed-feedback (DFB) fiber lasers are appealing sources for various applications, notably because they offer a combination of low linewidth and high power [1]. When operating in a regime of simultaneous emission of two orthogonal eigenstates, such short-cavity lasers can be considered as microwave-optical sources, since the typical beat frequency between the two polarization modes is in the GHz range [2][3][4][5][6][7][8][9]. In this context, the stabilization of the beat frequency, in order to reduce the phase noise in microwave photonic links, is a question that led recently to develop an optical phase-locked loop scheme [9], and to the use of frequency-shifted optical feedback [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has long been shown that these structures are capable of sustaining the oscillation of two orthogonal polarizations at different frequencies [2][3][4]. Such dual-frequency DFB fiber lasers were foreseen as efficient sensors [5], and may be promising as heterodyne sources in the field of microwave photonics [6][7][8][9]. However, in the context of optical distribution of local oscillators for instance, stabilization of the beat frequency against a reference is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…At variance with common solid-state lasers, where additional optical components can be inserted into the laser cavity, new techniques have here to be imagined in order to ensure, on the one hand, simultaneous and stable oscillation of the two polarizations and, on the other hand, possible phase locking of the beat note. Elasto-optical effects (torsion [7] or compression [8]) have already been tested to control the beat frequency of dual-polarization fiber lasers, but phase-locked stabilization to a reference oscillator has never been performed. Besides, optical feedback on a DBR laser also leads to efficient noise reduction [9].…”
Section: Introductionmentioning
confidence: 99%
“…Distributed feedback (DFB) fiber lasers are usually known to be single frequency but it has long been observed that DFB lasers can sustain the oscillation of two orthogonal polarizations at different frequencies [2][3][4] . Such dual-frequency DFB fiber lasers were used as sensors 5,6 , and may be promising as heterodyne sources in the field of microwave photonics [7][8][9][10] .However, in the context of optical distribution of local oscillators for instance, we can wonder whether DFB fiber laser can be used to realize a stable continuous-wave microwave source. Stabilization of the beat frequency against a reference is then mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of the beat frequency against a reference is then mandatory. Elasto-optical effects, induced by torsion 8 or compression 9 , have already been used to control the beat frequency of dual-polarization fiber lasers, but phase-locked stabilization to a reference oscillator has never been performed. More precisely, we are interested in an optical phase-locked loop (OPLL) where the DFB fiber laser acts as a voltage-controlled oscillator (VCO) driven by the laser pump power.…”
Section: Introductionmentioning
confidence: 99%